Teenage Births—Influence of Sexually Transmitted Diseases During Pregnancy [6M]. (May 2016) - Fuchs, Esther; Dwiggins, Maggie L.; Ren, Jinma; Aldag, Jean C.
Abstract : INTRODUCTION: Our county in Central Illinois has impressive rates of both teenage pregnancies and sexually transmitted infections (STIs). Prior studies have shown that both teenage birth and lower genital tract infection lead to a higher risk of preterm birth. The primary objective of our study was to determine the prevalence of STI's (Gonorrhea, Chlamydia and Trichomonas) in pregnant teenagers and compare teenagers with and without STIs in regards to preterm delivery and chorioamnionitis. METHODS: We performed a retrospective cohort study by reviewing electronic medical records of females age 19 or younger who delivered between 01/01/2012 and 12/31/14 at our tertiary referral center. Patients with multiple gestation were excluded. After descriptive statistics and univariate analysis, a multivariable logistic regression was used to examine the association between STIs and outcomes controlling for age, marital status, race, parity and smoking status. RESULTS: 562 charts were reviewed, 517 teens with live singleton births identified. The overall rate of STIs during pregnancy was 17.2% (gonorrhea 3.5%, chlamydia 14.7%, trichomonas 3.3%). The rates of preterm deliveries and clinical chorioamnionitis were 18.4% (95/517) and 4.1% (21/517), respectively. STIs were not associated with preterm deliveries or chorioamnionitis ( P >.05), but pregnant teenagers with preeclampsia were more likely to have preterm deliveries ( P <.01). CONCLUSION: Our rate of preterm deliveries (18.4%) was higher than the national average (11.4%), confirming a higher rate of preterm births in teenagers. Surprisingly, no significant association between STIs and preterm delivery was found in our population, in contrast to previous studies not specific to teenagers.